Anesthesia Blunts Carbon Dioxide Effects on Glymphatic Cerebrospinal Fluid Dynamics in Mechanically Ventilated Rats - Persson, Niklas Daniel Åke; Lohela, Terhi J.; Mortensen, Kristian Nygaard; Rosenholm, Marko; Li, Qianliang; Weikop, Pia; Nedergaard, Maiken; Lilius, Tuomas O. (Anesthesiology (Philadelphia), 2024)
Background Impaired glymphatic clearance of cerebral metabolic products and fluids contribute to traumatic and ischemic brain edema and neurodegeneration in preclinical models. Glymphatic perivascular cerebrospinal fluid flow varies between anesthetics possibly due to changes in vasomotor tone and thereby in the dynamics of the periarterial cerebrospinal fluid (CSF)–containing space. To better understand the influence of anesthetics and carbon dioxide levels on CSF dynamics, this study examined the effect of periarterial size modulation on CSF distribution by changing blood carbon dioxide levels and anesthetic regimens with opposing vasomotor influences: vasoconstrictive ketamine–dexmedetomidine (K/DEX) and vasodilatory isoflurane. Methods End-tidal carbon dioxide (ETco2) was modulated with either supplemental inhaled carbon dioxide to reach hypercapnia (Etco2, 80 mmHg) or hyperventilation (Etco2, 20 mmHg) in tracheostomized and anesthetized female rats. Distribution of intracisternally infused radiolabeled CSF tracer 111In-diethylamine pentaacetate was assessed for 86 min in (1) normoventilated (Etco2, 40 mmHg) K/DEX; (2) normoventilated isoflurane; (3) hypercapnic K/DEX; and (4) hyperventilated isoflurane groups using dynamic whole-body single-photon emission tomography. CSF volume changes were assessed with magnetic resonance imaging. Results Under normoventilation, cortical CSF tracer perfusion, perivascular space size around middle cerebral arteries, and intracranial CSF volume were higher under K/DEX compared with isoflurane (cortical maximum percentage of injected dose ratio, 2.33 [95% CI, 1.35 to 4.04]; perivascular size ratio 2.20 [95% CI, 1.09 to 4.45]; and intracranial CSF volume ratio, 1.90 [95% CI, 1.33 to 2.71]). Under isoflurane, tracer was directed to systemic circulation. Under K/DEX, the intracranial tracer distribution and CSF volume were uninfluenced by hypercapnia compared with normoventilation. Intracranial CSF tracer distribution was unaffected by hyperventilation under isoflurane despite a 28% increase in CSF volume around middle cerebral arteries. Conclusions K/DEX and isoflurane overrode carbon dioxide as a regulator of CSF flow. K/DEX could be used to preserve CSF space and dynamics in hypercapnia, whereas hyperventilation was insufficient to increase cerebral CSF perfusion under isoflurane. Editor’s Perspective What We Already Know about This Topic Cerebrospinal fluid flow via the perivascular glymphatic clearance pathway is important to maintain central nervous system homeostasis General anesthetics and carbon dioxide have major influence on cerebral vasomotor tone and, therefore, can influence glymphatic cerebrospinal fluid dynamics The combined influence of general anesthetics and varying carbon dioxide levels on cerebrospinal fluid dynamics is unexplored What This Article Tells Us That Is New In ventilated rats under physiologic carbon dioxide levels, ketamine–dexmedetomidine anesthesia led to cerebral vasoconstriction and concomitant increases in cerebrospinal fluid space size, whereas isoflurane anesthesia had opposite effects In hypercapnic conditions, ketamine–dexmedetomidine anesthesia preserved the total intracranial cerebrospinal fluid volume, and hyperventilation-induced hypocapnia did not change cerebrospinal fluid volume under isoflurane anesthesia These observations suggest that general anesthetics are potent modulators of cerebrospinal fluid space and can overcome the influence of carbon dioxide on cerebrospinal fluid dynamics In ventilated rats under physiologic carbon dioxide levels, ketamine–dexmedetomidine anesthesia led to cerebral vasoconstriction and concomitant increases in cerebrospinal fluid space size, whereas isoflurane anesthesia had opposite effects. In hypercapnic conditions, ketamine–dexmedetomidine anesthesia preserved the total intracranial cerebrospinal fluid volume, and hyperventilation-induced hypocapnia did not change cerebrospinal fluid volume under isoflurane anesthesia. These observations suggest that general anesthetics are potent modulators of cerebrospinal fluid space and can overcome the influence of carbon dioxide on cerebrospinal fluid dynamics.